O gênero Ocotea Aubl. (Lauraceae) na região centro-oeste do Brasil - Domingos, Daniel Quedes (2016)
Ocotea is the largest neotropical genus of the Lauraceae family, with approximately 350 species, and 172 found only in Brazil. The genus is among the largest, which most contributes for the richness of the flora in the many vegetation formations in Brazil. A taxonomic treatment for Ocotea in the Center-West region is presented here, consisting of identification key, descriptions, illustrations and comments, which include geographical distribution, ecology, state of conservation and time of flowering and fruiting. The study confirmed 20 species of Ocotea for the Center-West region, which occur in the most diverse forest formations, cerrado (lato sensu), rupestrian fields, Gallery Forest, Dryland Forest, Floodplain Forest, Deciduous Seasonal Forest, Semi-Deciduous Seasonal Forest and Ombrophilous Forest. Of the 21 registered species, 6 are new occurrences, with Ocotea acyphylla, Ocotea catharinensis and Ocotea puberula being new registries for Mato Grosso do Sul, Brazil, while for Mato Grosso, Ocotea glomerata is cited for the first time. Ocotea catharinensis and Ocotea notata are referenced for the first time in the Center-West region.